Identifying place meanings ascribed to the Baekdu-Daegan trail in South Korea. (15th March 2021) - Park, Jihee; Kyle, Gerard T.
Abstract: Using photo-based interviews with hikers who had completed hiking the Baekdu-Daegan (BD) trail in South Korea, this study investigated their place meanings ascribed to the trail and how mountain landscape attributes effect their meaning construction. Ten meaning-themes emerged from the analyses: aesthetic value, therapeutic value, challenging experience, nature conservation, connection to nature, social connections with people, self-discipline and spiritual growth, historical/cultural value, experience of the sacred and geopious feelings, and unique and symbolic hiking attraction . Findings revealed that the physical setting of the BD trail, its spatial features, and natural/social/historical/cultural attributes along the trail were the significant sources of meaning and attachment. One theme, in particular, geopiety, reflected a more intense association with the BD trail; a sense of awe and reverence, the arousal of love of country, and a desire for the reunification of South and North Korea.